(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Max Weber (1864-1920)revealed his major Sociological observation, of the Principle of Rationality. The Principle of Rationality consisted of two social movements, Substantive (traditional culture/inner world) and Formal Rationality (modern society, Money Economy(Outer world).